ANALYSIS OF INPATIENT STANDARDS (KRIS) PRATAMA NUSANTARA CLINIC - Purba, Ivan Elisabeth; Sinaga, Taruli Rohana; Adiansyah (Program Studi Ners UNIVERSITAS SARI MUTIARA INDONESIA, 2023)
The government has mandated that the JKN single-class system will be implemented in 2024. Currently, the Standard Inpatient Class at the Pratama Nusantara Health Medan Clinic (KRIS) has not been put into effect. The lack of implementation may be due to insufficient awareness, infrastructure, facilities, and workforce. To assess the readiness of the Pratama Nusantara Medan Clinic, this study examines its internal and external preparedness through qualitative research methods. The researcher's subjectivity is acknowledged, and data validity is ensured through triangulation methods, such as time extension, source triangulation, and data collection method triangulation. The study participants include the Head of the Clinic, the Health Services Section, the Jang Medium Section of Pratama Nusantara Health Clinic, Finance, and Patients. The data analysis employs SWOT, Fishbone, and VUCA models. The findings suggest that the Pratama Nusantara Medan Clinic is capable of adhering to the KRIS guidelines provided by DJSN. The Clinic's efforts to conduct outreach, maintain good patient relationships, enhance infrastructure, and expand inpatient buildings demonstrate its commitment to this policy and its positive impact on society.